Natural Gas-Fuelled, Spark-Ignited = 1 /Twc Engine - Takats, Michal (Communications - Scientific letters of the University of Zilina, 2001)
Description of the implementation of stoichiometric concept on natural gas-fuelled, spark-ignited engine for co-generation plant (CHP). Description of behavior of closed loop -control system and exhaust gas aftertreatment. Examples of optimization procedure and its results at particular engine concern its environmental properties, power and efficiency. Comparisons are made between the stoichiometric engine and lean burn one.